2012
DOI: 10.1590/s1806-37132012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Broncoespasmo induzido por exercício em corredores brasileiros de longa distância de elite

Abstract: Objective: To determine the prevalence of exercise-induced bronchoconstriction among elite long-distance runners in Brazil and whether there is a difference in the training loads among athletes with and without exercise-induced bronchoconstriction. Methods: This was a cross-sectional study involving elite long-distance runners with neither current asthma symptoms nor a diagnosis of exercise-induced bronchoconstriction. All of the participants underwent eucapnic voluntary hyperpnea challenge and maximal cardiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…This observation can be explained by the fact that, clinically, the symptoms of EIB might be confused with typical symptoms of exhaustion/dyspnea during exercise as a result of performing exercise at such intensive level, such as in a marathon. Nevertheless, the percentage of EIB+ found here in relation to marathon runners is in agreement with other studies [22,23], and is higher than in the general population [19][20][21]23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation can be explained by the fact that, clinically, the symptoms of EIB might be confused with typical symptoms of exhaustion/dyspnea during exercise as a result of performing exercise at such intensive level, such as in a marathon. Nevertheless, the percentage of EIB+ found here in relation to marathon runners is in agreement with other studies [22,23], and is higher than in the general population [19][20][21]23].…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that the prevalence of EIB among enrolled marathon runners was 23.6%, which is in agreement with other studies [19][20][21][22]. Based on this finding, the volunteers were distributed into two groups (EIB+ and EIB−), allowing us to evaluate the differences in pulmonary and aerobic capacities, as well as in the inflammatory response between these groups, in order to correlate such responses with marathon performance.…”
Section: Discussionsupporting
confidence: 91%
“…In light of this, the consensus is that moderate-intensity exercise is more suitable to achieve the benefits of physical training while minimizing asthma attacks in humans (33). In fact, some studies have shown a severe bronchospasm in response to high intensity exercise both in people with respiratory problems (34) and athletes (35, 36). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, 62% of the athletes considered allergic (AQUA+) claimed shortness of breath, cough and/or itchy throat during or following exercise (AQUA © question 13). The prevalence of EIB symptoms was higher than those observed in soccer players and recreational runners (11.7% and 32%, respectively) [6,7], and was even higher than in a study previously performed by our group that assessed the prevalence of EIB, using eucapnic voluntary hyperventilation (EVH), in elite long distance runners [17]. However, the lack of an objective assessment, such as EVH, may have influenced the higher prevalence of allergic symptoms that were observed in the present study compared to our previous study [17].…”
Section: Discussionmentioning
confidence: 57%
“…However, it seemed unnecessary because the AQUA © questionnaire has been previously validated based on its association with IgE levels, and demonstrating high specificity [6]. Moreover, according to our previous experience with elite runners [17], blood collection is not well accepted either by athletes or by their coaches due to possible doping concerns.…”
Section: Discussionmentioning
confidence: 99%